Investigation of Combined Aging and Mullins Stress Softening of Rubber Nanocomposites - Bakar, Mohamed; Sola-Wdowska, Marta; Przybyłek, Małgorzata; Białkowska, Anita; Zarzyka, Iwona; Hanulikova, Barbora; Masař, Milan (Polymers, 2024)
The present study investigated the effects of thermal aging, ultraviolet radiation (UV), and stress softening on the performance properties of rubber modified with Cloisite Na+ or Cloisite 20A. Tensile strength (TS), strain at break (SB), modulus, and the retention coefficient were measured before and after aging. Results showed that TS and SB decreased by about 50% after 7 days of aging for all tested samples due to the breakage of the chemical bonds between rubber and nanoparticles. The modulus at 300% elongation increased by 20%, 15%, and 7% after thermal aging for the unmodified sample, nanocomposites with Cloisite Na+, and Cloisite 20A, respectively. The shape retention coefficient of all samples was not affected by heat, except for the virgin rubber sample, which exhibited a decrease of about 15% under thermal aging. The virgin matrix and nanocomposites showed different values of aging coefficient during thermal aging and UV radiation. The dissipated energy of samples that were aged after stretching was slightly higher than that of samples that were aged after stretching due to the breakdown of the bonds within the nanocomposites. Loading-reloading energy results showed that the level of stress softening was lower when Mullins was applied after the aging of the samples. Differential scanning calorimetry results indicated a slight decrease in Tg1 in the aged and stretched samples and an increase in the temperature of the first endothermic peak due to the addition of nanofillers in the stretched and aged samples. Thermogravimetric analysis revealed that all tested samples exhibited similar thermograms, regardless of their state of stretching or aging. Scanning electron microscopy analysis showed that the fracture surface of the virgin unaged sample was rough with some holes, while it was flatter and less rough after aging.
Keywords: structure; Mullins effect; thermal properties; morphology; aging; rubber nanocomposites; mechanical properties